Fin Tech – A game changer, risks and return - Solanki , Akash (Gyan Management Journal, 2024)
Fin Tech revolution can be traced to the global financial crisis. In the Indian context, the Fin Tech revolution has been primarily in the field of payment systems and there has been a quantum increase in the last decade. Regulators have taken a number of regulatory initiatives for the development of Fin Tech landscape. The digital advancement is also fraught with risks pertaining to mis-selling, data privacy and online fraud. Therefore, in order to harness the potential of digital innovations, it is important there is need for spreading awareness among regarding risks associated with online/cyber transactions, there is also need for bolstering up the digital infrastructure and also cost effective technology to reach the under privileged sections of the society.